Advancements in rapid diagnostics and genotyping of Piscirickettsia salmonis using Loop-mediated Isothermal Amplification - Isla, Adolfo; Aguilar, Marcelo; Flores-Martin, Sandra N.; Barrientos, Claudia A.; Soto-Rauch, Genaro; Mancilla-Schulz, Jorge; Almendras, Felipe; Figueroa, Jaime; Yañez, Alejandro J. (Frontiers in Microbiology, 2024)
Introduction Piscirickettsia salmonis, the causative agent of Piscirickettsiosis, poses a significant threat to the Chilean aquaculture industry, resulting in substantial economic losses annually. The pathogen, first identified as specie in 1992, this pathogen was divided into two genogroups: LF-89 and EM-90, associated with different phenotypic mortality and pathogenicity. Traditional genotyping methods, such as multiplex PCR, are effective but limited by their cost, equipment requirements, and the need for specialized expertise. Methods This study validates Loop-mediated Isothermal Amplification (LAMP) as a rapid and specific alternative for diagnosing P. salmonis infections. We developed the first qPCR and LAMP assay targeting the species-conserved tonB receptor gene (tonB-r, WP_016210144.1) for the specific species-level identification of P. salmonis. Additionally, we designed two genotyping LAMP assays to differentiate between the LF-89 and EM-90 genogroups, utilizing the unique coding sequences Nitronate monooxygenase (WP_144420689.1) for LF-89 and Acid phosphatase (WP_016210154.1) for EM-90. Results The LAMP assays demonstrated sensitivity and specificity comparable to real-time PCR, with additional benefits including rapid results, lower costs, and simplified operation, making them particularly suitable for field use. Specificity was confirmed by testing against other salmonid pathogens, such as Renibacterium salmoninarum, Vibrio ordalii, Flavobacterium psychrophilum, Tenacibaculum maritimum, and Aeromonas salmonicida, with no cross-reactivity observed. Discussion The visual detection method and precise differentiation between genogroups underscore LAMP's potential as a robust diagnostic tool for aquaculture. This advancement in the specie detection (qPCR and LAMP) and genotyping of P. salmonis represents a significant step forward in disease management within the aquaculture industry. The implementation of LAMP promises enhanced disease surveillance, early detection, and improved management strategies, ultimately benefiting the salmonid aquaculture sector.